FULFILLMENT OF THE NEEDS OF YOUTH IN THE PROCESS SOCIOLOGY LEARNING DURING PANDEMIC - Liza Dwi Eftiza Khairunniza (JURNAL SOCIUS, 2022)
This research describes the facts that occur in the community or school and able to provide answers and solutions in dealing with the process learning to keep going well in the midst of the covid-19 pandemic seen from the fulfillment of the needs of teenagers at SMAN 2 Banjarmasin. This research aims: (1) to classify the needs of youth in SMAN 2 Banjarmasin, (2) Describe the forms of efforts to meet the needs of youth in the learning process on the subject of Sociology at SMAN 2 Banjarmasin, (3) Analyzing the fulfillment of adolescent needs in the learning process on the eyesSociology lessons during the Corona Virus Disease 2019 (Covid-19) pandemic at SMAN 2 Banjarmasin. The method used in this research is the method qualitative and data collection by purposive sampling. Collection technique with triangulation (combined), data analysis is inductive/qualitative, and the results Qualitative research emphasizes meaning rather than generalization. The results of the study show that (1) the needs of adolescents include:safety needs, physiological needs, needs for acceptance, needs to be appreciated, self-actualization needs, social needs, physical needs, the need for status, the need for achievement, and the need for venting (2) Educators have made various efforts to fulfill the needs of adolescents in the learning process in the subject of Sociology at SMAN 2 Banjarmasin preferring to use the learning method. Prepare different learning media from the meeting previously.